Implementation Of the Project-Based Learning Model In The Pancasila Education Subject For Class X Students At SMA Negeri 1 Malang - Syahri, Mohamad; Yusuf, Nurbani; Lutfiana, Rose Fitria; Diah Rosita, Pramita; Prasetyo Wibowo, Arif; Romadhon, Romadhon (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
This study aims to analyze the implementation, driving and inhibiting factors, and solutions provided in the implementation of the Project Based Learning learning model in the subject of Pancasila Education for grade X Students at SMA Negeri 1 Malang. The type and design of research is qualitative descriptive. The results of the study stated that the implementation of the Project Based Learning learning model in Pancasila Education lessons was carried out through two project implementations, including critical reasoning and cooperation projects, and the resulting products were posters and piggy banks. In the implementation of PjBL implementation in the classroom, several driving and inhibiting factors are obtained. The driving factors are learning becomes more flexible, discussions are more in-depth, and learning is more done in groups and presentations. While the inhibiting factors are, lack of activeness, creativity from some students, assignments that are considered too burdensome for students, costs that are felt to be quite a lot, and the duration of time needed is longer than class hours. The solution to deal with this obstacle is more intense assistance from the lesson teacher to less active students, forming student cohesiveness, minimizing costs, and carrying out reflection after the lesson is over